Importins involved in the nuclear transportation of steroid hormone receptors: In silico and in vitro data - Kalyvianaki, Konstantina; Panagiotopoulos, Athanasios A.; Patentalaki, Maria; Castanas, Elias; Kampa, Marilena (Frontiers in Endocrinology, 2022)
The nuclear receptor superfamily (NRS) consists of 48 receptors for lipophilic substances and is divided into 7 different subfamilies, with subfamily 3 comprising steroid hormone receptors. Several nuclear receptors usually bind their cognate ligands in the cytosol and the complex (mono- or dimerized) is transported to the nucleus, where it acts as a transcription initiating factor for a number of genes. The general structure of nuclear receptors consists of an N-terminal activating domain (A/B), important for the binding of activating or inhibitory co-factors, the DNA-binding domain (C), responsible for the association of the receptor-ligand-co-factor complex to the nucleus, the ligand-AF2 domain (E/F), where ligand binding occurs as well as that of ligand-dependent activating/inhibiting factors, and a flexible/non-structured domain (D), linking the DBD and LBD, called hinge region, on which a significant number of post-translational modifications occur. This hinge domain, for the sub-class of steroid receptors, is a non-structured domain and was reported as mainly responsible for the nuclear transport of steroid receptors, since it contains a specific amino acid sequence (Nuclear Localization Signal-NLS), recognized by importin α. In addition to the importin α/β complex, a number of other importins have been discovered and reported to be responsible for the nuclear transport of a number of significant proteins; however, the corresponding recognition sequences for these importins have not been identified. Recently, we have reported the identification of the NLS sequences for importins 4, 5 and 7. In this work, we provide in silico data, followed by experimental in vitro validation, showing that these alternative importins are responsible for the nuclear transportation of steroid hormone receptors such as ERα, AR and PR, and therefore they may consist of alternative targets for the pharmacological manipulation of steroid hormone actions. Moreover, we provide additional in silico data for the hinge region of steroid hormone receptors which is highly enriched with NLS sequences for importins 4, 5 and 7, in addition to the recognition NLS for importin α/β.